2008
DOI: 10.1055/s-0028-1090034
|View full text |Cite
|
Sign up to set email alerts
|

Systemische Akutpsychiatrie – erste Outcomevergleiche

Abstract: No significant outcome improvement could be determined after the team training and implementation of the additional interventions. Different suggestions to improve the intervention program are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…An outcome study of 187 patients enrolled in the SYMPA project demonstrated that this practice, including genuine systemic interventions (such as the joint planning of therapeutic goals and reflecting teams), was equally effective as a standard treatment comprising psychopharmacotherapy and psycho‐education (Crameri et al . ). The lack of change‐sensitive instruments for assessing benefits in the wider problem‐determined system and the very short distance between pre‐testing and post‐testing (28 days on average) may explain the lack of superior patient outcomes when compared to treatment as usual.…”
Section: Previous Outcome Research On Sympamentioning
confidence: 97%
“…An outcome study of 187 patients enrolled in the SYMPA project demonstrated that this practice, including genuine systemic interventions (such as the joint planning of therapeutic goals and reflecting teams), was equally effective as a standard treatment comprising psychopharmacotherapy and psycho‐education (Crameri et al . ). The lack of change‐sensitive instruments for assessing benefits in the wider problem‐determined system and the very short distance between pre‐testing and post‐testing (28 days on average) may explain the lack of superior patient outcomes when compared to treatment as usual.…”
Section: Previous Outcome Research On Sympamentioning
confidence: 97%
“…Von 2003 -2005 wurden 6 komplette Stationsteams (Pflegekräfte, Psychologen, Ärzte, Sozialarbeiter) parallel zur laufenden klinischen Tätigkeit hierarchieübergreifend weitergebildet [22]. Hinsichtlich des Therapieergebnisses der Patienten nach erfolgter Weiterbildung fand sich kein signifikanter Unterschied, obwohl in der Brief Psychiatric Rating Scale tendenziell höhere Effektstärken für die Interventionsgruppe beobachtet wurden [23] Aufgrund der inakzeptablen Ergebnisse in der Faktorenanalyse und bezüglich der internen Konsistenz in der letzten deutschen Validierungsstudie [32] wurden in dieser Untersuchung die Items der optional konzipierten Skala "Betroffenheit" aus dem Fragebogen entfernt. Für die übrigen 3 Skalen zeigten sich zufriedenstellende Ergebnisse der Faktorenstruktur und Konstruktvalidität.…”
unclassified